Plain missing - Miller, Emma (An Amish mystery, 2017)
"Inn owner Rachel Mast is no longer a devout member of the Amish community of Stone Mill, Pennsylvania, but she still cares deeply for them. So she's staying at her family's farm to help her mother through an illness--and at the same time, trying to track down two missing people"--